ANALISIS SELF-CONFIDENT DAN KECEMASAN TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI SPLDV SMP MEDAN - Manalu, Ayunasari; Aruan, Anggie Desi K.; Tambunan, Hardi; Pangaribuan, Firman (JURNAL CURERE, 2023)
This study aims to analyze self-confidence and anxiety about mathematical problem solving abilities to improve student learning outcomes in SPLDV material for class VIII SMP Negeri 3 Medan. This research is a causal correlation study using quantitative methods. The population of this research is all students of class VIII, with a total of 120 students. The data analysis method used is the path analysis method with the help of SPSS software. The results showed that there was a significant influence between self-confidence and anxiety on problem-solving abilities to improve student learning outcomes in class VIII SPLDV material at SMP Negeri 3 Medan.